KEMAMPUAN PENGENALAN DASAR-DASAR KOMPUTER SEBAGAI STRATEGI ADAPTASI PENDIDIKAN DI KOTA JAYAPURA PROPINSI PAPUA - Ferry Rhendra P.P. Sitorus; Alfred A.M. Padwa (JURNAL PENGABDIAN PAPUA, 2020)
The training program on the introduction of computer basics was aimed at several students around the Polda-Bhayangkara Housing, Waena Kampung, Buper Kampung, Heram District, Jayapura City, Papua Province. The training activity on the intro-duction of basic computer was directed at students in this region because most of them came from outside the City of Jayapura. With the origin and quality of previous school settings that were not as advanced as the quality of education in Jayapura City. The training on the introduction of basic computer was carried out for eight meetings with a total meeting time of three hours per meeting. The students who attended this meeting were as many as ten trainees. The training participants are given a material guide to the introduction of word computer basics. Furthermore, the training participants practiced the teaching materials in the eight meetings. Because of the training on the introduction of computer basics, some trainees have gained simple and practical insights and skills for the introduction of computer basics. Simple and practical insights and skills in the introduction of the basics of computers include the benefits of using the word application in the execution of tasks in their school and campus, the skills to activate and deactivate computers or laptops, the introduction of function fingers in typing, the introduction of functions and menus in word facilities, the skills to type a number of words and sentences, skills to correct sentences that have been typed, as well as the storage skills of typing results in certain sections or folders. Through the training on the introduction of computer basics, participants get technical skills that are in accordance with the adaptation process in their education level. With these skills the participants have at least been able to do simple script writing for activities and reporting assignments in their school and campus. Keywords: Adaptation, basic computer training, students